Predictive role of polymerase chain reaction in the early diagnosis of congenital Trypanosoma cruzi infection - Velazquez, Elsa (2014)
Fil: Velázquez, Elsa B. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.